2020
DOI: 10.1097/inf.0000000000002734
|View full text |Cite
|
Sign up to set email alerts
|

Birth Testing for Infant HIV Diagnosis in Eswatini: Implementation Experience and Uptake Among Women Living With HIV in Manzini Region

Abstract: Introduction: HIV testing at birth of HIV-exposed infants (HEIs) may improve the identification of infants infected with HIV in utero and accelerate antiretroviral treatment (ART) initiation. Methods: ICAP at Columbia University supported implementation of a national pilot of HIV testing at birth (0–7 days) in Eswatini at 2 maternity facilities. Dried blood spot (DBS) samples from neonates of women living with HIV (WLHIV) were collected and processed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Clinicians cited high workload, lack of space in ANC/ MCH, and lack of systems for adequately tracking mother-infant pairs prior to 6-weeks as challenges to implementing at birth POC. Other studies have found that maintaining coverage over weekends and holidays [45], seeking delivery and postnatal care at different facilities [46], long turnaround times and low rates of linkage to care among infants diagnosed as HIV-positive [47] to be challenges for at birth PCR; while lack of consensus on who should test and where the testing should occur [43] and shortage of trained staff [30] have been cited as challenges to POC testing for EID.…”
Section: Plos Onementioning
confidence: 99%
“…Clinicians cited high workload, lack of space in ANC/ MCH, and lack of systems for adequately tracking mother-infant pairs prior to 6-weeks as challenges to implementing at birth POC. Other studies have found that maintaining coverage over weekends and holidays [45], seeking delivery and postnatal care at different facilities [46], long turnaround times and low rates of linkage to care among infants diagnosed as HIV-positive [47] to be challenges for at birth PCR; while lack of consensus on who should test and where the testing should occur [43] and shortage of trained staff [30] have been cited as challenges to POC testing for EID.…”
Section: Plos Onementioning
confidence: 99%
“…At-birth and point-of-care (POC) HIV testing for infants can streamline infant HIV testing and diagnosis. At-birth testing (using conventional polymerase chain reaction [PCR]) can reduce infant age at HIV diagnosis [8,9] while POC testing can reduce turnaround times for results to < 1 day [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, both with POC and not, BT has been found to be generally acceptable among mothers and HCWs [ 23 , 24 ]. Similar to this study, other studies have found parental concern about pricking newborns [ 23 , 24 ], but in general BT was considered to be in the best interest of the child and the benefits seen to outweigh the concerns. Similar to this study, a study in Kenya reported that POC BT can improve newborn care and reduce parental anxiety [ 25 ].…”
Section: Discussionmentioning
confidence: 90%